Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s10753-018-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Somatostatin Analogue Octreotide on Rheumatoid Arthritis Synoviocytes

Abstract: Somatostatin and its analogues are known to have modulatory effects on immune response and their anti-proliferative, anti-angiogenic, and analgesic properties make them attractive candidates for a therapeutic use in immune-mediated diseases, such as rheumatoid arthritis. Here, we demonstrate the ability of the somatostatin analogue octreotide to inhibit interleukin-15 and to increase interleukin-10 production by rheumatoid arthritis fibroblast-like synovial cells maintained in a chronic inflammatory state. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Somatostatin sst2 receptors dominate in human monocytes and macrophages (Dalm et al, 2003). Sst2 receptor agonist octreotide inhibits release of inflammatory cytokines (TNF-α, IL-6, and IL-15) from synoviocytes of RA patients, offering a plausible mechanism for the anti-inflammatory effect of GYY4137 (Casnici et al, 2018). Besides, sensory neuron-derived opioid peptides might contribute to antinociceptive action, too (Pethő et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatin sst2 receptors dominate in human monocytes and macrophages (Dalm et al, 2003). Sst2 receptor agonist octreotide inhibits release of inflammatory cytokines (TNF-α, IL-6, and IL-15) from synoviocytes of RA patients, offering a plausible mechanism for the anti-inflammatory effect of GYY4137 (Casnici et al, 2018). Besides, sensory neuron-derived opioid peptides might contribute to antinociceptive action, too (Pethő et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“… 23 Another possibility could be an inhibitory effect on purinergic signaling. 24 Despite the antinociceptive effect, an anti-inflammatory action was lacking with relation to paw swelling. Previously, systemic octreotide treatment (10 µg/kg) in rats did not affect edema following mustard oil injection in the paw.…”
Section: Discussionmentioning
confidence: 99%
“…These cells can secrete multiple proinflammatory cytokines and mediators, regulate the expression of growth factors, trigger more FLS activation as feedback, and lead to the destruction of cartilage [18]. Recently, many studies have found that FLS is a very crucial and effective treatment for RA [11,[19][20][21]. Therefore, to illustrate the effect of USP5 on RA, we used FLS cells in the present study, and we found that the expression of USP5 was enhanced in RA-FLS compared with OA-FLS.…”
Section: Discussionmentioning
confidence: 99%